MENINGKATKAN PEMAHAMAN KONSEP MATEMATIKA SISWA DENGAN PENERAPAN THE POWER OF TWO - Dina Oktarina (Jurnal Edukasi dan Penelitian Matematika, 2018)
Understanding  of  mathematical  concepts  is  a  basic  capabilities  that  must  be  improved  in  students.  In  fact, understanding  of  mathematical  concepts  in  class  VIII  SMPN  18  Padang  is  still  low.  The  solutions  to  resolve  it  by applying active learning model of The Power of Two. Type of research is quasy experiment with the static group design. Sample  research  is  taken  by  simple  random  sampling.  The  result  showsthat  students’understanding  of  mathematical concepts by applying active learning model of The Power Of Twois better than students’understanding of mathematical conceptsby applyingconventional learning. It can be concluded that active learning model of The Power of Two gives positive influences towards to understanding of mathematical concepts.Keywords – conventional learning,mathematical concepts, the power of two